Di-jet production in gamma gamma collisions at LEP2 - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (2008)
The production of two high-PT jets in the interactions of quasi-real photons in e + e - collisions at √S ee from 189 GeV to 209 GeV is studied with data corresponding to an integrated e + e - luminosity of 550 pb-1. The jets reconstructed by the k ⊥ -cluster algorithm are defined within the pseudo-rapidity range -1<η<1 and with jet transverse momentum, pT , above 3 GeV/c. The differential di-jet cross-section is measured as a function of the mean transverse momentum PT of the jets and is compared to perturbative QCD calculations. © 2008 Springer-Verlag / Società Italiana di Fisica.